Assessing greenhouse gas emissions in hospitals: The development of an open-access calculator and its application to a German case-study - Claudia Quitmann; Leonard Terres; Andy Maun; Rainer Sauerborn; Emma Reynolds; Till Bärnighausen; Alina Herrmann; Bernd Franke (Cleaner Environmental Systems)
Hospitals are major contributors to climate change. It is therefore essential to identify the main sources of hospitals’ greenhouse gas (GHG) emissions to develop and monitor mitigation measures. Yet, a transparent and comprehensive hospital-specific GHG accounting methodology is currently lacking. We have developed a hybrid methodology that follows the GHG Protocol Corporate Accounting and Reporting Standard to calculate emissions. We used bottom-up approaches to scope 1 and 2 and, where feasible, to scope 3. Due to data scarcity, we used top-down approaches for several scope-3-categories. As a case study demonstration, we applied this methodology to a German university hospital: Scope 3 accounted for the majority of GHG emissions (164,529 t CO2e (71%)), while scopes 1 (6008 t CO2e (3%)) and 2 (60,565 t CO2e (26%)) contributed less. Methodological challenges remain, such as a limited accuracy and monitoring options for top-down approaches. Nonetheless, this case study demonstrates that the developed methodology supports hospitals in measuring GHG emissions as part of their regulatory requirements and responsibility to safeguard planetary health.